Efektivitas LKPD Scaffolding Question Prompt untuk Meningkatkan Self-Efficacy Siswa pada Pembelajaran IPA Materi Struktur Bumi - Ramadhaniar, Sahira; Indayati, Tatik; Sari, Devi Novita (Jurnal Pendidikan Ilmu Pengetahuan Alam (JP-IPA), 2025)
This study aims to determine the effectiveness of Scaffolding Question Prompt-based Student Worksheets (LKPD) in improving students' self-efficacy in science learning on the topic of Earth Structure. This study used a quantitative descriptive design involving 30 students of grade VIII-B at MTs Alif Laam Miim Surabaya in the 2024/2025 academic year. Data were collected using a self-efficacy questionnaire developed based on Bandura's indicators and measured using a five-point Likert scale. Data were analyzed descriptively using percentage categorization and statistically using Paired Sample Test. The results showed an increase in the average self-efficacy score from 62.00 (pretest) to 83.33 (posttest) with a significance value of 0.000 (0.05), indicating a significant difference before and after treatment. The categorical shift from "moderate" to "high-very high" further confirms the increase. Therefore, Scaffolding Question Prompt-based LKPD is effective in strengthening students' self-efficacy and supporting more active and independent science learning.